Investigating EFL Learners’ Perception of English Journal Article Structure - Asmawati, Andi; Indah Fadhilah Rahman; Multazam Abubakar; Suhrah (ELTIES : English Language Teaching for EFL Learners Journal, 2025)
This study examines the perceptions of EFL learners in the Islamic Education Department regarding reading English journal articles, with a particular focus on affective, cognitive, and behavioural aspects. This study employed a descriptive quantitative method involving 54 respondents. Data were collected via an online questionnaire distributed using Google Forms, which included Likert-scale items. The data were analyzed using simple percentage-based descriptive statistics. The findings revealed that while a majority of students did not have high anxiety in reading English articles, a substantial proportion still perceived English journal articles as difficult. Cognitively, most students understood the purpose and structure of articles, though a smaller group struggled with detailed structural awareness. Behaviorally, students reported benefits such as vocabulary improvement and acknowledged the importance of English journal articles, though only some consistently completed readings or compared article structures. These insights suggest that although students generally recognize the relevance of English journal articles to their academic growth, targeted support is still needed to address specific affective and cognitive barriers to their use.